Colombia : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Colombia has enjoyed strong growth over the past several years, among the highest in Latin America. Credible fiscal and inflation targeting frameworks have supported sound macroeconomic policy management, which underpinned robust economic performance during the last decade. Social indicators have improved steadily over this period. Public debt remained low. The current account deficit widened to 5.2 percent in 2014, but capital inflows were buoyant. Growth is expected to gradually rise toward its potential over the medium term, supported by the government's public-private partnership-based infrastructure program and a gradual recovery in oil prices and external demand.